The Influence of Environmental Understanding on Environmental Concern in Biology Education Students - Indah Putri (Journal of Academic Biology and Biology Education, 2026)
Purpose of the study: This study aims to analyze the influence of environmental understanding on environmental concern among Biology Education students at Alauddin State Islamic University Makassar. Methodology: A quantitative correlational design was employed involving 120 students selected through proportional random sampling. Data were collected using a validated Likert-scale questionnaire and analyzed using descriptive statistics, Pearson correlation, and simple linear regression. Main Findings: The findings show a significant positive relationship between environmental understanding and environmental concern (r = 0.69, p < 0.05), with regression results indicating that environmental understanding significantly predicts environmental concern (Y = 19.44 + 0.78X). Novelty/Originality of this study: This study highlights the integration of scientific environmental knowledge with Islamic ethical values in shaping environmental concern, specifically among biology education students in an Islamic higher education context.